Turbo Marketing - Susanta, Susanta (Jurnal Ilmu Administrasi dan Bisnis, 2005)
In to day tight competitive market, marketer must able to delivery product to the customers speedily. Speed becomes a key success of the company. If a company fails to reach their customer at the fist,. their competitors will do. Turbo Marketing is a new trend in marketing that emphasizes speed in the process of delivering product to the customers. Turbo marketing is the spreading concept from responsiveness in the service delivery. Fact indicated that, when customers find the contact employee more responsive fir the experience, what is delivered is most important to evaluation of service quality, satisfaction, and behavioral intention. When company thought to be more responsive, how the service is delivered is essential to customerâs evaluations. 1Mzen responsiveness is perceived as speed delivery, turbo marketing plays a large role in influencing customer satisfaction whit the service experience. Key word: turbo marketing, customerâs value, value chain